(untitled) (Journal of Academic Finance, 2017)
The use of accounting has evolved, and its utility becomes essential, for the importance of the services that it can deliver as means of economic calculation and management. It becomes a means of collecting quantified information, an instrument for analyzing and assisting in the control of the effectiveness of management, and thus constitutes an "information system" essential to the management of the company. This work has outlined the main concepts of the information system and accounting which is a fundamental instrument of this system.